Pengaruh Sistem Pengendalian Intern, Kompetensi Sumber Daya Manusia, dan Penerapan Akuntansi Berbasis Akrual pada Kualitas Laporan Keuangan - Jesica Prastiwi, Ni Putu; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2018)
This study aims to determine the effect of internal control systems, human resource competencies, and the application of accrual based accounting on the quality of financial statements. This study uses an associative quantitative approach which aims to determine the relationship between internal control systems, human resource competencies, the application of accrual-based accounting with the quality of financial statements. This study using conducted non-probability sampling method, namely by using a purposive sampling technique using 100 samples. Methods of data collection for this study is survey methods with questionnaires. Hypotheses test use logistic regression to predict the probability of the occurrence of an event that match the data on the logit logistic curve function. The results show that the internal control system has a positive influence on the quality of financial statements in the Regional Financial and Asset Management Agency of Bali Province. Human resource competency has a positive influence on the quality of financial reports Regional Assets of the Province of Bali. Keywords : internal control system, human resource competence, application of accrual-based accounting, quality of financial statements